11+5u=-7+13u

Simple and best practice solution for 11+5u=-7+13u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+5u=-7+13u equation:


Simplifying
11 + 5u = -7 + 13u

Solving
11 + 5u = -7 + 13u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-13u' to each side of the equation.
11 + 5u + -13u = -7 + 13u + -13u

Combine like terms: 5u + -13u = -8u
11 + -8u = -7 + 13u + -13u

Combine like terms: 13u + -13u = 0
11 + -8u = -7 + 0
11 + -8u = -7

Add '-11' to each side of the equation.
11 + -11 + -8u = -7 + -11

Combine like terms: 11 + -11 = 0
0 + -8u = -7 + -11
-8u = -7 + -11

Combine like terms: -7 + -11 = -18
-8u = -18

Divide each side by '-8'.
u = 2.25

Simplifying
u = 2.25

See similar equations:

| f(x)=5x^2-10x+7 | | 6x^4+2x^2=0 | | .9(x-1000)/200 | | y=6x^2-12x+4 | | 4x-1/2=0 | | 8x^2/(2x)^3 | | 10+3(2xz+3y+2xz)= | | 4x^2+19x+22= | | 7x-5=4(0)-6 | | (X^3)-6.75X+2.7= | | 2*8=84 | | 4(5c-1)-3=18c+3 | | 7(0)-5=4y-6 | | (2x-4)=6(x-12) | | 0=5x^2+5x-10 | | (a+4)=144 | | -3(t+4)=6 | | 2/7-2/53 | | 62/93= | | 14g=54 | | 23+3y-7=10y-9-2y | | -1.5(x+2)=12 | | 1364-1209= | | 15a^3+15a^2+5= | | (4x-1)2=196 | | 15a^3-15a^2+5= | | 3xy^2-7x^2+x+3x^2= | | 17765/646= | | 136/93= | | 31/3w=200 | | 3x(x-5)=14 | | 7a-3a+=14 |

Equations solver categories